2020
DOI: 10.34172/jrip.2021.06
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between blood lead level and anemia in hemodialysis patients

Abstract: Introduction: Studies show that blood lead level (BLL) is higher in hemodialysis patients than in healthy people. Lead can disrupt iron metabolism and hemoglobin synthesis and therefore it is regarded as a cause of anemia. Objectives: This study investigated the relationship between BLL and anemia in end-stage renal disease (ESRD) undergoing maintenance hemodialysis Patients and Methods: This case-control study was conducted on 70 patients who had received hemodialysis at least for three months. The participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A significant negative correlation between HD duration and Hb levels was reported in this investigation (Figure 1). Mohammadi et al, 2021 published their findings, which revealed a significant correlation between hemoglobin and ferritin levels (P <0.001), as well as a correlation between hemodialysis duration (4.62±4.0 years) and serum iron (P=0.001) [29].…”
Section: Discussionmentioning
confidence: 96%
“…A significant negative correlation between HD duration and Hb levels was reported in this investigation (Figure 1). Mohammadi et al, 2021 published their findings, which revealed a significant correlation between hemoglobin and ferritin levels (P <0.001), as well as a correlation between hemodialysis duration (4.62±4.0 years) and serum iron (P=0.001) [29].…”
Section: Discussionmentioning
confidence: 96%